Shared spaces and "throwntogetherness" in later life: A qualitative GIS study of non-migrant and migrant older adults in Singapore. Issue 124 (August 2021) - Ho, Elaine L.E.; Liew, Jian An; Zhou, Guo; Chiu, Tuen Yi; Yeoh, Brenda S.A.; Huang, Shirlena
Highlights: Interactions between non-migrants and migrants inflect their ageing experiences. The spatial attributes of shared spaces can deter or foster intercultural relations. Micro-publics reveal whether meaningful co-presence exists in shared space. Ageing-in-place needs to be analysed alongside ageing-across-borders. Qualitative GIS methods provide a fuller perspective of older adults' life-worlds. Abstract: While there has been considerable academic interest in the topics of encounters and conviviality, including within the migration literature, little is known about how non-migrant and migrant older adults interact with one another in shared spaces, forming micro-publics that inflect the experiences of ageing for both groups. Using Qualitative Geographic Information Science (qualitative GIS), this paper identifies three types of spaces shared by non-migrant and migrant older adults from Singapore and the People's Republic of China respectively. The first type of shared space is characterised by asynchronicity in that, despite co-located activities, intercultural interactions are less likely to be fostered between non-migrants and migrants. The second type of shared space features informal, spontaneous encounters that develop into more regular forms of interaction with 'otherness', but active negotiation of social difference could be limited. The third type of shared space is marked by formal, organised activities where non-migrants and migrants work towards a common goal, prompting productive negotiations with difference. Through juxtaposing these three types of shared spaces, we argue for the importance of drawing out how spatial attributes can deter or foster varying degrees of negotiations with difference, while acknowledging that the fluidity of such processes depend on the users and social contexts too. We also suggest that notions of ageing-in-place need to be analysed alongside ageing-across-borders, giving attention to how migration impacts ageing in later life—both for migrants who are adapting to life abroad temporarily as well as non-migrants who may experience "transnationalism by proxy". (247 words; max 250 words)